Evaluation of Four Castor Bean (Ricinus communis L.) Varieties for Yield and Oil Production in Colombia - Hurtado-Salazar, Alejandro; Gutiérrez, Germán; Restrepo, José Fernando; Costa Nobre, Danúbia Aparecida (Agrociencia Uruguay, 2013)
The castor bean (Ricinus communis L.) is an alternative to production because of its great potential for oil production. It has many uses and the possibility of producing biodiesel. This fuel can contribute to reducing petroleum consumption. This study aimed to evaluate four varieties from different areas: two from Ecuador («Negro» and «Blanca jaspeada»), one from Valle del Cauca, and another one («Violeta») from coffee zone of the municipality of Manizales in Colombia. The experiment was conducted in Palestina Township, Caldas department, 1010 masl. We used a randomized block design with four replications. Each block consisted of 36 plants and each plot had nine plants. Seven months after planting pruning was performed 50 cm from the ground looking for a renovation and smaller size of the plants because of the height they had reached (> 3.5 m), and initiating new assessments (second cycle) four months after pruning. In both cycles there were significant differences for seed weight, bunch dry weight, seed number and yield. The genotype «Blanca jaspeada» was superior, with a yield of 3.5 t/ha-1 while «Violeta» genotype yielded 0.72 t/ha-1, but was, however, the best for oil content with 36.7%. The financial analysis showed that for «Blanca jaspeada» the benefit/cost rate was higher, with a return of 2.14 cents per dollar invested.